Better Epitope Discovery, Precision Immune Engineering, and Accelerated Vaccine Design Using Immunoinformatics Tools - De Groot, Anne S.; Moise, Leonard; Terry, Frances; Gutierrez, Andres H.; Hindocha, Pooja; Richard, Guilhem; Hoft, Daniel Fredric; Ross, Ted M.; Noe, Amy R.; Takahashi, Yoshimasa; Kotraiah, Vinayaka; Silk, Sarah E.; et al. (Frontiers in Immunology, 2020)
Computational vaccinology includes epitope mapping, antigen selection, and immunogen design using computational tools. Tools that facilitate the in silico prediction of immune response to biothreats, emerging infectious diseases and cancers can accelerate the design of novel and next generation vaccines. Over the past 20 years, vaccinologists, bioinformatics experts, and advanced programmers based in Rhode Island, USA have developed an integrated toolkit for vaccine design called iVAX, that is secure and user-accessible by internet. This integrated set of immunoinformatic tools comprises algorithms for scoring and triaging candidate antigens, selecting immunogenic and conserved T cell epitopes, re-engineering or eliminating regulatory T cell epitopes, and re-designing antigens to induce immunogenicity and protection against disease for humans and livestock. Commercial and academic applications of iVAX have included identifying immunogenic T cell epitopes in the development of a T-cell based human multi-epitope Q fever vaccine, designing novel influenza vaccines, identifying cross-conserved T cell epitopes for a malaria vaccine, and analyzing immune responses in clinical vaccine studies. Animal vaccine applications to date have included viral infections of pigs such as swine influenza A, PCV2 and African Swine Fever. “Rapid-Fire” applications for biodefense have included a demonstration project for Lassa Fever. As recent infectious disease outbreaks underscore the significance of vaccine-driven preparedness, iVAX stands ready for accelerated and rational design of genome-derived, epitope-driven vaccines.